Russia : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper describes economic developments in the Russian Federation during 1995-96. It reviews trends in the domestic economy. It describes developments in the public finances, monetary policy, financial sector, and the external sector. The paper highlights that the output decline slowed to 4 percent in 1995, the smallest decline since the beginning of the transition. The decline accelerated to 6 percent in 1996, with lower investment-generally attributed to the uncertainty associated first with the presidential elections and subsequently with the President's health being a major source of the decline.